IMPROVING STUDENTS’ SKILL IN WRITING SHORT PARAGRAPH BY USING SIMPLE PRESENT TENSE AT FIRST SEMESTER STISIP PERSADA BUNDA PEKANBARU - Lia Diana (Journal of English Language and Education, 2019)
The study purposes to determine whether writing short paragraph by using present tense can improve the students’ writing skill. In this research, the writer focuses on the students’ simple present tense mastery and the ability to write a short paragraph. The research intents onto the students’ ability English functional writing, especially in writing simple paragraph the first semester Sekolah Tinggi Ilmu Sosial dan Politik (STISIP) Persada Bunda Pekanbaru. The participants are the first semester students of Sekolah Tinggi Ilmu Sosial dan Politik (STISIP) Persada Bunda Pekanbaru. There were 13 students. The research found that writing short paragraph by using simple present tense could improve the students writing’s skill. This research is a qualitative research. The writer collected the data employ the test and the documentation technique. The test is written test of simple paragraph in English subject for the students at the first semester of STISIP Persada Bunda Pekanbaru. Then, the students’ sheet were corrected by scoring rubric of short paragraph by using simple present tense. Finally, the writer analyzes the students’ score.